First-principles study of Cd-doped germanium nanoclusters: Stability, electronic structure, and chemical properties - Anusha Rajan; Muthu Kumar; Prince Makarios Paul S; Vikash Mishra; Ravi Kumar Trivedi (Next Materials)
In the present study highlights the structural, electronic and chemical behavior of Cd doped germanium nanocluster Cd@Gen (n = 1–10) using the density functional theory (DFT). Notably, the Cd@Ge4, and Cd@Ge7 cluster exhibits exceptional stability, as evidenced by a significant high binding energy as 1.76 eV, and 1.94 eV, a large HOMO-LUMO gap 1.99 eV, and 1.94 eV with enhanced second-order energy difference. These both clusters also show a lower chemical potential −4.61 eV and 4.39 eV, moderate chemical hardness of 0.99 eV, and 0.97 eV, increases softness and high electrophilicity exhibiting favorable reactivity. Density of states analysis also confirms strong hybridization between Cd and Ge atoms, with Ge contributing significantly. These findings suggest their potential in nanoelectronics and catalysis.